Model for online teaching tools based on interpersonal, visual and verbal intelligence - Mohamad, Siti Nurul Mahfuzah (2014)
Multiple Intelligences (MI) are eight different ways to demonstrate intellectual ability. It is how human learn best and apply to daily activities.This study mainly aims to develop an Online Multiple Intelligence Teaching Tools (On-MITT) for the polytechnic lecturers and students. These teaching tools can assist lecturers to create their own teaching materials without having any knowledge of programming. The theory of Multiple Intelligences was used in this research. Certain studies have shown that teaching which tailors student‟s strength by using MI has many benefits while other studies revealed that there is a cause and effect between intelligence and academic achievement. The objectives of the research are to check whether there is a relationship between the students self-perceived MI and their academic achievement among the polytechnic students, design and develop On-MITT, evaluate the effectiveness of On-MITT in order to increase lecturers‟ motivation in teaching online as well as evaluate the effectiveness of teaching and learning using On-MITT. The population are 412 and the sample of the study comprised of 149 lecturers from the Malaysian Polytechnics from Jabatan Matematik, Sains dan Komputer (JMSK) and involved 69 diploma students in electrical course. There were 36 students in the experimental group who were taught with On-MITT and 33 students in the control group who were taught using traditional classroom. Data were gathered using Ujian Diagnostik Kecerdasan Pelbagai (UMI), Motivation Survey Questionnaire, Interview, and Classroom Observation as well as Teaching and Learning Survey Questionnaire. Findings of the study showed there is a significant positive linear relationship between Interpersonal (IN), Bodily- Kinesthetic (BK), Verbal-Linguistic (VL), Musical-Rhythm (MR), Visual-Spatial (VS), Naturalist (NA) intelligence and academic achievement. The results also revealed that the lecturers‟ motivation was not significantly affected by their teaching experience but affects by others factors such as knowledge, perceptions and skills. Students from the experimental group showed a higher achievement when compared with the control group. Overall, the findings showed that the On-MITT has motivational value, user friendly interface and interactivity design that can be used for all educators in technical education.